Benzoylation of anisole over silicotungstic acid modified mesoporous alumina - Selvakumar, S.; Singh, A. P. (Catalysis Letters, 2009)
Mesoporous alumina (MA) molecular sieves were synthesized by using aluminum sec-butoxide as Al precursor and lauric acid as the structure directing agent. The synthesized MA was functionalized with silicotungstic acid (STA) via wet impregnation method and characterized by various physico-chemical techniques. The XRD patterns of a series of HPA functionalized MA are showing the ordered structures. N(2) sorption analysis shows type IV isotherm. NH(3)-TPD measurements revealed an increase in number of acid sites with an increase in loading of STA over MA. At the same time decrease in the acidity was observed with the increase in calcination temperature of the supported materials. Functionalization of STA were also carried out over different alumina supports such as catapol-B (CB) and alumina synthesized without surfactant (ASW) and their activities were evaluated by carrying out liquid phase Friedel-Craft acylation (FC) reaction of anisole with p-toluoyl chloride in a batch reactor at 120 degrees C. Recycling was performed in the FC reaction using 30 wt% STA-MA two times and no major deactivation of the catalyst was observed.
Keywords: Friedel-Craft acylation; Mesoporous alumina; Silicotungstic acid